Rancang Bangun Smart Farming Untuk Observasi Pertumbuhan Tanaman Kangkung Dengan Dukungan Teknologi Sonic Bloom - Rezeki, Putri Ayu; Dewanta, Favian; Astuti, Sri (MULTINETICS, 2022)
Water spinach is one of the popular vegetables in Indonesia because it has fast-growing properties and is relatively fast in harvesting. Currently, some farmers are cultivating water spinach hydroponically because the technique is more efficient. In the growth of kale, farmers usually always look directly at the garden. So to see from a distance, a water spinach growth monitoring test will be carried out using the Internet of Things (IoT) combined with sonic bloom technology taken from dangdut, jazz, and murottal music with a frequency of 4000 Hz. Sonic Bloom is a technology development that utilizes sound waves to accelerate the opening of the leaf mouth (stomata). The parameters for testing the productivity of water spinach were plant height, room temperature, and water temperature. Network performance testing parameters are delay, throughput, and packet loss. The purpose of this study was to compare the results of three types of music that affect water spinach and water spinach without sonic bloom technology and to test the results of network performance. The application of sonic bloom technology was successfully implemented on water spinach with the most influential result being jazz music with a height of 25.47 cm. Very good network performance in this study is testing with delivery every 5 minutes in 30 minutes of observation with a distance of 2 meters with a delay value of 28.34 ms, throughput 71010.70 bps and packet loss of 0%.